Blasphemy and Social Conflict in Abrahamic Religions: Historical Dynamics and Political Implications in Indonesia - Purnama, Tata Septayuda; Darajat, Deden Mauli; Rumaru, Shulhan (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. This paper emphasizes the relationship between historical perspectives, social conflict, and political implications in cases of blasphemy in Abrahamic religions, with a focus on Indonesia as a case study. The main issue discussed is how blasphemy in Abrahamic religions can trigger social conflict through the interplay of theological interpretations, identity politics, and historical grievances. This study uses a historical qualitative approach combined with critical discourse analysis, with data collected through library research on primary and secondary historical documents, such as books, journals, and archives related to blasphemy against Abrahamic religions in Indonesia and worldwide. The research process involves analyzing the social, political, and cultural contexts of each historical period to understand the dynamics of change and continuity in cases of religious blasphemy. The findings reveal that responses to religious blasphemy are strongly influenced by social and political contexts, particularly the instrumentalization of blasphemy accusations for power consolidation. Legal and mediation approaches in Indonesia, such as the role of the Indonesian Ulema Council (MUI), have proven effective in mitigating conflicts and maintaining religious harmony. This study concludes that collective efforts to enhance religious literacy and interfaith dialogue must be supported by structural reforms in blasphemy laws to prevent conflicts and preserve social harmony. Keywords: Blasphemy, social conflict, religious literacy, Indonesia, mediation. Abstrak. Artikel ini menekankan hubungan antara perspektif historis, konflik sosial, dan implikasi politik dalam kasus penistaan pada agama samawi, dengan fokus pada Indonesia sebagai studi kasus. Permasalahan utama yang dibahas adalah bagaimana penistaan dalam agama samawi dapat memicu konflik sosial melalui interaksi interpretasi teologis, politik identitas, dan persaingan historis. Penelitian ini menggunakan pendekatan kualitatif historis yang dikombinasikan dengan analisis wacana kritis, dengan data dikumpulkan melalui studi pustaka pada dokumen historis primer dan sekunder, seperti buku, jurnal, dan arsip terkait penistaan agama di Indonesia dan dunia. Proses penelitian melibatkan analisis konteks sosial, politik, dan budaya pada setiap periode sejarah untuk memahami dinamika perubahan dan kontinuitas kasus-kasus penistaan agama. Hasil penelitian menunjukkan bahwa respons terhadap penistaan agama sangat dipengaruhi oleh konteks sosial dan politik, khususnya politisasi tuduhan penistaan untuk konsolidasi kekuasaan. Pendekatan hukum dan mediasi di Indonesia, seperti peran Majelis Ulama Indonesia (MUI), terbukti efektif dalam meredam konflik dan memelihara kerukunan umat beragama. Penelitian ini menyimpulkan bahwa upaya kolektif dalam meningkatkan literasi agama dan dialog antaragama harus didukung reformasi struktural pada UU penodaan agama untuk mencegah konflik dan memelihara keharmonisan sosial. Kata Kunci: Penistaan agama, konflik sosial, literasi keagamaan, Indonesia, mediasi.